1985
DOI: 10.1524/ract.1985.38.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects in Hot Replacement by Recoil Halogens

Abstract: Recoil ^'Cl/Hot atom chemistry IHot repiacement/Benzene derivatives SummaiyThe effect of the second substituent on the repiacement of Cl, F, NO, and OH in benzene derivatives by recoil "O was studied. The results show that the chemical nature as well as the relative Position of the second substituent in the benzene ring are of significance, except in the case of "Cl-for-F repiacement.A clear distinction between the different factors Controlling the energetic reactions of recoil halogens in Condensed systems ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…[1] some conclusions could be drawn with regard to the energy range and possible mechanisms of the high energy replacements studied. Thus we assumed the formation of a short-lived excited intermediate between the recoiling 38 C1, 125 I and 211 At -reacting in an energy range not higher than a few eV -and the aromatic molecule, a finding well in line with some earlier studies [6][7][8].…”
Section: Introductionsupporting
confidence: 75%
“…[1] some conclusions could be drawn with regard to the energy range and possible mechanisms of the high energy replacements studied. Thus we assumed the formation of a short-lived excited intermediate between the recoiling 38 C1, 125 I and 211 At -reacting in an energy range not higher than a few eV -and the aromatic molecule, a finding well in line with some earlier studies [6][7][8].…”
Section: Introductionsupporting
confidence: 75%
“…Thus, the yields of labile tritium increase from 19% in CuTPP to 29% in free H 2 TPP, as free H 2 TPP contains the scavenger in a molecule. A similar function was observed in recoil halogen reactions [10] and was termed the self-scavenger (internal scavenger), where the OH group of phenol acts as a scavenger for the recoil 38 CI atom in the aromatic compounds and CC1 4 system.…”
Section: Methodsmentioning
confidence: 79%
“…[8] who have observed almost the same *C1-for -CI substitution yields 55%) for C 6 H S C1 and C 6 F 5 C1 and also by those of BEREI etal. [9] for C 6 H 5 C1 and o-C 6 H 4 FCl 25%) systems (the dose received by the samples in the former case was 7.5 kGy compared with 0.1 kGy in the latter).…”
Section: Resultsmentioning
confidence: 90%
“…BEREI etal. [9], in their study using the intramolecular competition of recoil 38 CI atoms for heavy atoms or group replacement in substituted chlorobenzenes, clearly showed that the substitution of CI, NO2 or OH is strongly dependent upon the nature and the relative position of the second substituent, whereas the yields of F-for -CI and CI-for -F substitutions are independent. Since further investigations in this direction help in understanding the effect of the nature and position of the second substituent, the present study deals with the reactions of recoil 38 C1 atoms with different substituted halobenzenes.…”
Section: Introductionmentioning
confidence: 99%